If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6c + -1) + -16 = 34c + 6 Reorder the terms: 6(-1 + 6c) + -16 = 34c + 6 (-1 * 6 + 6c * 6) + -16 = 34c + 6 (-6 + 36c) + -16 = 34c + 6 Reorder the terms: -6 + -16 + 36c = 34c + 6 Combine like terms: -6 + -16 = -22 -22 + 36c = 34c + 6 Reorder the terms: -22 + 36c = 6 + 34c Solving -22 + 36c = 6 + 34c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-34c' to each side of the equation. -22 + 36c + -34c = 6 + 34c + -34c Combine like terms: 36c + -34c = 2c -22 + 2c = 6 + 34c + -34c Combine like terms: 34c + -34c = 0 -22 + 2c = 6 + 0 -22 + 2c = 6 Add '22' to each side of the equation. -22 + 22 + 2c = 6 + 22 Combine like terms: -22 + 22 = 0 0 + 2c = 6 + 22 2c = 6 + 22 Combine like terms: 6 + 22 = 28 2c = 28 Divide each side by '2'. c = 14 Simplifying c = 14
| -18n+8=-14n-12 | | 6/4+2w=-2/w-10 | | 2x^3-12x^2+18x+3=0 | | 2(2c-1)-2=2c+8 | | 5y-15y=-31-39 | | (2c+3)/(2c+6)=1/c | | 32-12=5(x-3) | | 15x+-12-8x-6-3=0 | | v^2+15v-16=0 | | -6(t+3)=6 | | 6x-5y=19 | | 16y^3-8x^2= | | 15x+-12-8-6-3=0 | | 16x^3-8y^2= | | 6x-7=7x+3 | | P=i^2xr | | -4+2x^2+-8x=2x^2+8 | | 4x+2x+-6-5=17 | | 4x^2-28x=-2x^2-5x-15 | | -7(x+2)-44=6-15 | | 3(x-2)+4=1+4x | | 20=9t-19t | | 7(x-1)=2x+5 | | 4z=16-44 | | 7x^3+6x^2-16x=0 | | 100=20q-2q^2 | | 5x/6=3x/8+10 | | 2x+2=48 | | -6-3=5y+10 | | 4+3d=25-4d | | 8h-3=10h-9 | | x^2-2x^2-5x+14=0 |